Electrical nerve stimulation for sensory-neural pathway reconstruction in upper-limb amputees - Wang, Yingying; Liu, Hongyu; Zeng, Peiying; Ji, Lingchao; Zhou, Yaqi; Zhou, Liufang; Tao, Yuan (Frontiers in Neuroscience, 2023)
Introduction The loss of the neural sensory function pathways between the stump limbs and the brain greatly impacts the rehabilitation of limb function and the daily lives of amputees. Non-invasive physical stressors, such as mechanical pressure and transcutaneous electrical nerve stimulation (TENS), could be potential solutions for recovering somatic sensations in amputees. Previous studies have shown that stimulating the residual or regenerated nerves in the stumps of some amputees can produce phantom hand sensations. However, the results are inconclusive due to unstable physiological responses caused by inaccurate stimulus parameters and positions. Methods In this study, we developed an optimal TENS strategy by mapping the distribution of the nerves in the stump skin that elicitsphantom sensations known as a “phantom hand map.” We evaluated the effectiveness and stability of the confirmed stimulus configuration in a long-term experiment using single- and multi-stimulus paradigms. Additionally, we evaluated the evoked sensations by recording electroencephalograms (EEG) and analyzing brain activities. Results The results demonstrated that various types of intuitive sensations for amputees could be stably induced by adjusting TENS frequencies, particularly at 5 and 50 Hz. At these frequencies, 100% stability of sensory types was achieved when the stimuli were applied to two specific locations on the stump skin. Furthermore, at these locations, the stability of sensory positions was 100% across different days. Moreover, the evoked sensations were objectively supported by specific patterns of event-related potentials in brain responses. Discussion This study provides an effective method for developing and evaluating physical stressor stimulus strategies, which could play an important role in the somatosensory rehabilitation of amputees and other patients suffering from somatomotor sensory dysfunction. The paradigm developed in this study can provide effective guidelines for stimulus parameters in physical and electrical nerve stimulation treatments for a variety of symptoms related to neurological disorders.